We Are the Earth and the Earth Is Us: How Palates Link Foodscapes, Landscapes, Heartscapes, and Thoughtscapes - Provenza, Frederick D.; Anderson, Cindi; Gregorini, Pablo (Frontiers in Sustainable Food Systems, 2021)
Humans are participating in the sixth mass extinction, and for the first time in 200,000 years, our species may be on the brink of extinction. We are facing the greatest challenges we have ever encountered, namely how to nourish eight billion people in the face of changing climates ecologically, diminish disparity between the haves and the have-nots economically, and ease xenophobia, fear, and hatred socially? Historically, our tribal nature served us well, but the costs of tribalism are now far too great for one people inhabiting one tiny orb. If we hope to survive, we must mend the divides that isolate us from one another and the communities we inhabit. While not doing so could be our undoing, doing so could transform our collective consciousness into one that respects, nourishes, and embraces our interdependence with life on Earth. At a basic level, we can cultivate life by using nature as a model for how to produce and consume food; by decreasing our dependence on fossil fuels for energy to grow, process, and transport food; and by transcending persistent battles over one-size-fits-all plant- or animal-based diets. If we learn to do so in ways that nourish life, we may awaken individually and collectively to the wisdom of the Maori proverb Ko au te whenua. Ko te whenua Ko au: I am the land. The land is me. In this paper, we use “scapes” —foodscapes, landscapes, heartscapes, and thoughtscapes—as unifying themes to discuss our linkages with communities. We begin by considering how palates link animals with foodscapes. Next, we address how palates link foodscapes with landscapes. We then consider how, through our reverence for life, heartscapes link palates with foodscapes and landscapes. We conclude with transformations of thoughtscapes needed to appreciate life on Earth as a community to which we belong, rather than as a commodity that belongs to us.